2014
DOI: 10.1080/15504263.2014.924772
|View full text |Cite
|
Sign up to set email alerts
|

Contingency Management for Patients With Dual Disorders in Intensive Outpatient Treatment for Addiction

Abstract: Objective This project investigated the effectiveness of contingency management for improving retention in treatment and positive outcomes among patients with dual disorders in intensive outpatient treatment for addiction. Methods The effect of contingency management was explored among a group of 160 patients exposed to contingency management (n = 88) and not exposed to contingency management (no contingency management, n = 72) in a partial hospitalization program. Patients referred to the partial hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…Participants enrolled in the CM condition were approximately twice as likely to remain in treatment longer than those in the control condition. 55 However, this study found no significant differences between participants in the CM and control conditions in levels of depression, anxiety, stress, drug cravings, coping ability, or number of drug-abstinent days. In a larger study reported by McDonell et al in 2013, outpatients with SMI receiving CM for stimulant drug abstinence, participants randomized to the CM condition were 2.4 times more likely than controls to submit a stimulant-negative urine sample during treatment.…”
Section: Resultscontrasting
confidence: 60%
“…Participants enrolled in the CM condition were approximately twice as likely to remain in treatment longer than those in the control condition. 55 However, this study found no significant differences between participants in the CM and control conditions in levels of depression, anxiety, stress, drug cravings, coping ability, or number of drug-abstinent days. In a larger study reported by McDonell et al in 2013, outpatients with SMI receiving CM for stimulant drug abstinence, participants randomized to the CM condition were 2.4 times more likely than controls to submit a stimulant-negative urine sample during treatment.…”
Section: Resultscontrasting
confidence: 60%
“…Regarding illicit drug use disorders, studies were reported on CM reducing marijuana use (Kaminer et al, 2014; Stanger et al, 2009) among adolescents, and psychomotor stimulant and poly-drug use among those with co-morbid mental illness (García-Fernández et al, 2013; Kelly et al, 2014; McDonell et al, 2013; Petry et al, 2013), socioeconomic disadvantage (Secades-Villa et al, 2013), pregnant women and mothers of young children (Schottenfeld et al, 2011), sexual minorities (specifically men who have sex with men, Menza et al, 2010; Reback et al, 2010), those with HIV infection (Petry et al, 2010), and military veterans (Hagedorn et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Also, new models, such as effective practices in community supervision (the "EPICS" model), have been developed to teach probation and parole officers evidence-based principles of effective behavioral management (53). Unlike cognitive-behavioral therapies for criminal thinking, however, behavioral management principles are often used by mental health professionals within residential and day programs for persons with co-occurring mental illness and substance use disorders (54,55). These observations provide a clear rationale for mental health-criminal justice collaboration in planning and treatment, including deciding who is responsible for providing which treatments and services for each client.…”
Section: What Workmentioning
confidence: 99%